Role of the Attachment Style in Determining the Association Between Headache Features and Psychological Symptoms in Migraine Children and Adolescents. An Analytical Observational Case–Control Study. Issue 2 (6th January 2017) - Tarantino, Samuela; De Ranieri, Cristiana; Dionisi, Cecilia; Gagliardi, Valentina; Paniccia, Maria Francesca; Capuano, Alessandro; Frusciante, Roberto; Balestri, Martina; Vigevano, Federico; Gentile, Simonetta; Valeriani, Massimiliano
Abstract : Objective: We aimed to study the role of attachment style on headache severity and psychological symptoms in migraineurs children/adolescents. Moreover, we investigated the association between attachment style, migraine severity, and psychological symptoms. Background: Attachment theory suggests that early interpersonal relationships may be important determinants of psychopathology and pain management. In particular, individuals with insecure attachment styles have been shown to experience more pain than people with secure attachment style. Few studies focused on headache and data on attachment style in pediatric headache are scarce. Methods: We studied 90 migraineurs (mean age 12.2 ± 2.6 years; female: 54, male: 36). Patients were divided in two groups according to headache attack frequency: (1) high frequency (HF) patients, having from weekly to daily episodes and (2) low frequency (LF) patients, showing ≤3 episodes per month. According to headache attack intensity, patients were classified in two groups: (1) mild pain (MP), allowing the patient to continue his/her daily activities and (2) severe pain (SP), leading to interruption of patient activities or forcing the child to go to bed. The psychological screening was assessed by SAFA Anxiety, Depression, and Somatization questionnaires. Attachment style was measured by the semi‐projective test Separation Anxiety Test. Patients were divided into "secure, " "avoidant, " "ambivalent, " and "disorganized/confused" attachment patterns. Results: We found a significant relationship between the attachment style and migraine features. The ambivalent attachment was the most common style among patients reporting high attack frequency (51%) and severe pain intensity (50%). Anxiety (SAFA‐A Tot: F  = 23.3, P  < .001), depression (SAFA‐D Tot: F  = 11.8, P  < .001), and somatization (SAFA‐S Tot: F  = 10.1, P  < .001) were higher in patients with ambivalent attachment style. Moreover, our results showed an association between high attack frequency and high anxiety levels, in children with ambivalent attachment style ( F  = 6.7, P  < .002). Conclusions: Ambivalent attachment style may be a common vulnerability factor that impacts on pain severity, anxiety, depression, and somatization symptoms in young migraineurs. In particular, the present study provides the first evidence of the role of insecure attachment on the relationship between pain severity and psychological symptoms in migraine children.